EMBR-01. MOLECULAR AND CLINICAL HETEROGENEITY IN HISTOLOGICALLY-DIAGNOSED CNS-PNET PATIENTS PROSPECTIVELY TREATED AS A SINGLE ENTITY: A REPORT FROM THE CHILDREN'S ONCOLOGY GROUP ACNS0332 TRIAL. Issue 2 (22nd June 2018) - Hwang, Eugene; Kool, Marcel; Burger, Peter; Capper, David; Chavez, Lukas; Brabetz, Sebastian; Williams-Hughes, Chris; Billups, Catherine; Heier, Linda; Jaju, Alok; Michalski, Jeff; Li, Yimei; et al.
Abstract: INTRODUCTION: Children with high-risk medulloblastoma, supratentorial primitive neuroectodermal tumor (CNS-PNET) and pineoblastoma (PBLs) have poor survival and were enrolled in this prospective trial. However, subsequent molecular profiling uncovered diagnostic discrepancies not detectable at protocol inception. Outcomes for patients with CNS-PNET/PBL are reported here. METHODS: In this phase 3 trial, children aged 3–22 years with newly-diagnosed CNS-PNET/PBL were randomly assigned to receive carboplatin during radiation and/or adjuvant isotretinoin after standard intensive therapy. DNA methylation profiling was retrospectively completed in patients with sufficient tissue. RESULTS: Out of eighty-five participants with institutionally-diagnosed CNS-PNETs/PBLs, 60 patients underwent molecular analysis. 31/60 were non-pineal in location, of which 22 (71%) represented tumors not intended for trial inclusion, including 18 high-grade gliomas (HGG), two atypical teratoid rhabdoid tumors, and two ependymomas. Retrospective central review was more consistent with molecular diagnosis, but maintained the discrepancy in some cases. Outcomes across tumor types were strikingly different. Patients with supratentorial embryonal tumors/PBLs exhibited 5-year event-free (EFS) and overall survival (OS) of 62.8% (95%CI, 43.4%-82.2%) and 78.5% (95%CI, 62.2–94.8%), respectively, while patients with molecularly-classified HGG had EFS/OS of 5.6% (95%CI, 0%-13.0%) and 12.0% (95%CI, 0%-24.7%), respectively. Neither carboplatin nor isotretinoin significantly altered outcomes. Survival for patients with HGG was similar to historic studies without craniospinal irradiation or intensive chemotherapy. CONCLUSIONS: For patients with CNS-PNETs/PBLs, prognosis is considerably better than previously assumed when molecularly-confirmed HGG are removed. Identification of HGG may spare children from unhelpful intensive treatment. This trial highlights the challenges of histology-based diagnosis and indicates that molecular profiling should become a standard component of initial diagnosis.